1984
DOI: 10.1073/pnas.81.8.2317
|View full text |Cite
|
Sign up to set email alerts
|

Proteins related to the mouse L-cell major heat shock protein are synthesized in the absence of heat shock gene expression.

Abstract: 70,000 (hsc70), which are present in unstressed mouse L cells in the absence of detectable hsp68 gene expression. After heat shock, the rapid rate of de novo hsp68 synthesis is a consequence of the new high steady-state concentration of hsp68 mRNA. MATERIALS AND METHODSCell Culture and Heat Shock Conditions. Mouse L cells (WT-4) were grown in alpha Eagle minimal essential medium with 10% fetal calf serum. Drosophila melanogaster Schneider line 2 (SN-2) cells were grown at 25°C in D22 medium containing 2% fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…The 70-kD protein occurred as a major charge species of pI 5.9, as estimated by comparison with the known isoelectric points of aAz-crystallin (pI 5.92; 11), lens 3' actin (pI 5.45; 29), and vimentin (pI 5.35; 38). The molecular weight and isoelectric point of this rat lens stress protein are in good agreement with published values for the major mammalian heat shock-induced proteins (hsp70), which range between Mr 66,000 and 72,000, and pI 5.6 and 6.3 (26,34,44,48). Also the position after two-dimensional gel electrophoresis of the rat lens 70-kD protein relative to actin, tubulin, and vimentin corresponds very well with published patterns for the major heat shock-or stress-induced protein in other cell types, in culture, or in vivo (6,15,19,26,44).…”
Section: Characterization Of the Heat-induced Rat Lens Proteinssupporting
confidence: 73%
See 2 more Smart Citations
“…The 70-kD protein occurred as a major charge species of pI 5.9, as estimated by comparison with the known isoelectric points of aAz-crystallin (pI 5.92; 11), lens 3' actin (pI 5.45; 29), and vimentin (pI 5.35; 38). The molecular weight and isoelectric point of this rat lens stress protein are in good agreement with published values for the major mammalian heat shock-induced proteins (hsp70), which range between Mr 66,000 and 72,000, and pI 5.6 and 6.3 (26,34,44,48). Also the position after two-dimensional gel electrophoresis of the rat lens 70-kD protein relative to actin, tubulin, and vimentin corresponds very well with published patterns for the major heat shock-or stress-induced protein in other cell types, in culture, or in vivo (6,15,19,26,44).…”
Section: Characterization Of the Heat-induced Rat Lens Proteinssupporting
confidence: 73%
“…The lens protein of 71 kD, of which the synthesis increased upon heat shock, can reasonably be identified as P73 (15,26,49), a constitutive protein present at considerable levels in many investigated normal cell types, and of which the synthesis is indeed stimulated by heat shock. It has been shown that P73 is closely related to SP71 (15,26).…”
Section: Characterization Of the Heat-induced Rat Lens Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other five of these 18 SP-proteins (EGF-like repeat and discoidin I-like domain-containing protein 3, Putative phospholipase B-like 2 isoform 1, Prominin-2, Ezrin and Syntaxinbinding protein 2) have been related with sperm capacitation [63][64][65][66][67]. Heat shock cognate 71 kDa is a protein related to environmental or physiological stresses [68] synthesized by sperm cells [69] that has been recently related to boar sperm cryotolerance [70]. Finally, Ectonucleotide pyrophosphatase/phosphodiesterase family member is an ATPhydrolyzing enzyme described in epididymis suggesting that this protein could be involved in the modulation of the epididymal environment [71].…”
Section: Discussionmentioning
confidence: 99%
“…Densitometric scanning of the autoradiograph indicated an approximately fivefold increase in expression of the 70-kDa protein and two-to threefold increases of the 89-and 74-kDa bands at 43°C. Proteins of these sizes have been identified previously as heat shock products in mammalian cells (5,15,16,22,24,25). In melanogaster, it is thought that at least one protein interacts with the heat shock regulatory region located upstream from the 5' end of the heat shock genes (29,38,39).…”
mentioning
confidence: 99%